The role of Saeed Nursi in service to Islamic sciences - Rekawt Salih Mohammed; Adnan Abdul Qader Kamil (QALAAI ZANIST JOURNAL, 2024)
Sheikh Saeed Nursi dedicated all his life to creating a project called saving the faith of the believer and the servant of the Qur’an, and in this project, he still changed the imitation faith which remains behind means a firm faith, for a true and living faith, and he give a great importance to the resurrection of the religious science and the faith. Which was near death and destruction, in the Arab and Islamic world in general and especially the Ottoman empire was in a state of weakness and defeat, as they said they were under the cultural power of Europe and the invaders, because of the feeling of all sheikh Saeed Nursi, who defended faith and rescuted Islam. He started calling for all Muslims to join the faith and science, and he also called for the construction and foundation of some institutions A way to study and Islamic science such as creating schools and universities, and by taking courses and instructing them, starting writing books, newspapers, and any place that is needed and encouraging Muslims and believers to learn the science of war in a modern, new and practical way. And with that, he faced protests, expulsion, arrests, and suffering by The Enemies of Islam, which at that time most of the Islamic shia were banned, and there was a big plan for Islam and Muslims. And happily, Saeed Nursi succeeded and reached the top of the call and his message. And this is because of this belief in self-determination, patience, cleanliness, and neutrality, without any financial and worldly material. As a result, he was able to reach out to the Islamic world and the islamic science in all fields, by spreading beliefs and science in all areas of Turkey, and by providing many scholars and readers from inside and outside The Islamic Republic to serve the holy Religion of Islam